Transformasi Lingkungan Pendidikan Islam sebagai Pusat Inovasi Keilmuan Akuntansi: Studi Evaluasi Kesiapan Digital dan Strategi Pengembangannya - Novi Riani; Andrian Anwar L Nata (SITASI: Journal of Islamic Studies and Inclusive Education, 2026)
This study aims to analyze the role of the educational environment as a dynamic hub and a center for generating thought and knowledge in accounting. The research employs a Mixed-Methods Sequential Explanatory design (quantitative bibliometric analysis followed by qualitative interviews to elaborate on the quantitative findings). The results indicate that the educational environment has transformed from a mere venue for delivering material into an active space that fosters new ideas, evidenced by a 139.8% increase in the number of publications and a rise in quality reflected in an average citation index increase from 2.1 to 4.3. This study concludes that the educational environment holds a strategic role in renewing and enriching the body of accounting knowledge. Consequently, policy support and cross-sector collaboration are essential to ensure the sustainability of this role and to provide tangible benefits for the advancement of accounting science and practice.